2019
DOI: 10.1111/scs.12766
|View full text |Cite
|
Sign up to set email alerts
|

Using sensor‐based technology for safety and independence – the experiences of people with dementia and their families

Abstract: Background The majority of people with dementia prefer to live independently and safely in their own home cared for by their family members. Much effort has been invested in the development of technology, such as sensor‐based networks. Many challenges remain, in particular gaining more knowledge about their experiences and perceived benefits. This study aimed to explore experiences, needs and benefits with using sensor‐based technology for safety and independence in the homes of people with dementia and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The third and final theme was support and independence, whereby attendees posited the benefits of technology and AI as being a supportive enabler. Literature suggests that technology can promote the independence of people living with dementia, for example, sensor technology as a safety precaution (Malmgren-Fänge et al, 2020). It can also result in decreased carer burden through feeling reassured that technology is assisting in the monitoring and management of the condition (for example, medication reminders, orientation devices and environmental detectors) (Boger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The third and final theme was support and independence, whereby attendees posited the benefits of technology and AI as being a supportive enabler. Literature suggests that technology can promote the independence of people living with dementia, for example, sensor technology as a safety precaution (Malmgren-Fänge et al, 2020). It can also result in decreased carer burden through feeling reassured that technology is assisting in the monitoring and management of the condition (for example, medication reminders, orientation devices and environmental detectors) (Boger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The safety and wellbeing for PwD often superseded ethical considerations in regards to the decision for implementation of ATT [28,36,40,45,47,58]. Dugstad et al (2019) found that ATT implementation within nursing homes facilities fostered a "safety culture", which bolstered the feeling of "saving lives" [33].…”
Section: Safety For the Pwdmentioning
confidence: 99%
“…A qualitative study by Fange et al (2020) [40] explored the experiences, needs and benefits with using sensorbased technologies for safety and independence in the homes of PwD and their family members (n = 30) [40]. Participants were recruited from the TECH@HOME project (n = 640) (2016-2019) in Sweden and found that ATT was viewed as a support to make life easier and safer [58].…”
Section: Safety For the Pwdmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensor technology has been reported to make life easier and safer for PwDs and their families [48]. However, active sensor technology such as social alarms has been reported to be challenging for people with cognitive decline, and passive sensor technology may therefore be a solution [10].…”
Section: Factors Associated With Access To Attmentioning
confidence: 99%